Structural perturbations in proton-randomized single point charge simulated ice - M.Pratt, Ronald (2001)
Molecular dynamics, along with Monte Carlo methods, continue to be powerful tools to probe molecular behavior: In this study, we used a simulation cell consisting of 896 water molecules in an ice-lh configuration to compare structural properties of protonrandomized simulated ice using the Single Point Charge (SPC) potential model. A subtle, significant crystal defect is found in proton-randomized ice which involves two of the three mutually perpendicular dipole angle distributions. This deformity does not influence macroscopic behavior of the substance, but it does indicate a departure in arrangement from the known structure of water: It is therefore recommended that an ordered ice structure first be set up, and then random perturbations made to achieve a proton disordered structure